Laporan Praktek Kerja Lapangan Penyusunan Dan Pengarsipan Surat - Mahfuzhi, AR Walad; Apridiansyah, Yovi; Giova, Giova; Setiawan, Arif; Felix, Igor (Jurnal Dehasen Mengabdi, 2023)
General election is a procedure and mechanism for delegating people's sovereignty to state administrators (legislative, executive and judiciary). Before the reform era, elections were carried out by the General Elections Institute (LPU) of the Ministry of Home Affairs, but since the reform era, elections have been held by an independent institution, namely the General Elections Commission which was formed based on amendments to the 1945 Constitution of the Republic of Indonesia article 22E paragraph (5) that general elections are held by an election commission which is national, permanent and independent in nature. The method used is a qualitative method which explains the preparation and filing of letters. Field work practice (PKL) at the Bengkulu provincial KPU office. The street vendors were carried out for 40 days, a lot of experience, knowledge and other things were obtained in the implementation of the street vendors. During the Field Work Practice (PKL) activities, I was able to find out firsthand how the activities were in practice at the Bengkulu provincial KPU office.